2021
DOI: 10.1016/j.celrep.2020.108614
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Modeling and Single-Nucleosome Tracking Reveal Remodeling of Clutch Folding and Dynamics in Stem Cell Differentiation

Abstract: Highlights d Mesoscale modeling of the Pou5f1 gene shows cell-typespecific nucleosome clutch patterns d H2B dynamics is cell-type specific and correlates with nucleosome clutch patterns d Linker histone H1 plays an important role in regulating H2B dynamics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 96 publications
11
47
0
Order By: Relevance
“…Superresolution and single molecule fluorescence imaging studies have shown that nucleosomes compact into 30-50 nm clutches (Ricci et al, 2015), which further assemble into domains of ~100-300 nm in radius (Ashwin et al, 2019;Itoh et al, 2021;Lakadamyali and Cosma, 2020;Nozaki et al, 2017b;Otterstrom et al, 2019). Analyses of their motion has shown that individual nucleosomes move within these domains on tens of milliseconds timescales (Gómez-García et al, 2021;Lerner et al, 2020), and the domains themselves move on hundreds of milliseconds to seconds timescales (Ashwin et al, 2019;Hajjoul et al, 2013;Itoh et al, 2021;Levi et al, 2005;Marshall et al, 1997;Nozaki et al, 2017b). In both regimes, movement is subdiffusive and/or confined (Ashwin et al, 2019;Gómez-García et al, 2021;Hajjoul et al, 2013;Itoh et al, 2021;Levi et al, 2005;Marshall et al, 1997;Nozaki et al, 2017a), in part due to constraints on a given chromatin segment imparted by adhesions to surrounding structures, which increase with length of the segment (i.e.…”
Section: Bridging Fluid Condensates To Chromatin Dynamics In the Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Superresolution and single molecule fluorescence imaging studies have shown that nucleosomes compact into 30-50 nm clutches (Ricci et al, 2015), which further assemble into domains of ~100-300 nm in radius (Ashwin et al, 2019;Itoh et al, 2021;Lakadamyali and Cosma, 2020;Nozaki et al, 2017b;Otterstrom et al, 2019). Analyses of their motion has shown that individual nucleosomes move within these domains on tens of milliseconds timescales (Gómez-García et al, 2021;Lerner et al, 2020), and the domains themselves move on hundreds of milliseconds to seconds timescales (Ashwin et al, 2019;Hajjoul et al, 2013;Itoh et al, 2021;Levi et al, 2005;Marshall et al, 1997;Nozaki et al, 2017b). In both regimes, movement is subdiffusive and/or confined (Ashwin et al, 2019;Gómez-García et al, 2021;Hajjoul et al, 2013;Itoh et al, 2021;Levi et al, 2005;Marshall et al, 1997;Nozaki et al, 2017a), in part due to constraints on a given chromatin segment imparted by adhesions to surrounding structures, which increase with length of the segment (i.e.…”
Section: Bridging Fluid Condensates To Chromatin Dynamics In the Cellmentioning
confidence: 99%
“…Analyses of their motion has shown that individual nucleosomes move within these domains on tens of milliseconds timescales (Gómez-García et al, 2021;Lerner et al, 2020), and the domains themselves move on hundreds of milliseconds to seconds timescales (Ashwin et al, 2019;Hajjoul et al, 2013;Itoh et al, 2021;Levi et al, 2005;Marshall et al, 1997;Nozaki et al, 2017b). In both regimes, movement is subdiffusive and/or confined (Ashwin et al, 2019;Gómez-García et al, 2021;Hajjoul et al, 2013;Itoh et al, 2021;Levi et al, 2005;Marshall et al, 1997;Nozaki et al, 2017a), in part due to constraints on a given chromatin segment imparted by adhesions to surrounding structures, which increase with length of the segment (i.e. number of adhesions) (Chubb et al, 2002;Hajjoul et al, 2013).…”
Section: Bridging Fluid Condensates To Chromatin Dynamics In the Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleosomes within disordered chromatin are proposed to form heterogeneous groups of variable sizes and densities—interspersed with nucleosome-free regions 23 . Furthermore, the density of nucleosomes, rather than the structure of the 30-nm fiber, is what seems to distinguish different chromatin regions (e.g., nucleosome density is higher in heterochromatin than in euchromatin) 16 , 23 , and change upon differentiation 24 . Sequencing-based methods that can resolve chromatin interactions in situ at single-nucleosome resolution—i.e., micrococcal nuclease chromosome conformation assay (Micro-C) 25 , 26 , ionizing radiation-induced spatially correlated cleavage of DNA with sequencing (RICC-seq) 27 , and high-throughput chromosome conformation capture with nucleosome orientation (Hi-CO) 28 —suggest that the irregular organization of chromatin is underpinned by dominant interactions among i and i ± 2 nucleosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these parameters can independently enable chromatin polymorphism, triggering the folding of 10-nm fibers into irregular loops, hairpins, and bends 21 . Indeed, irregular nucleosome spacing 21 , 32 , nucleosome-free regions 23 , 24 , 32 – 34 , heterogeneous on/off dyad binding of linker histone proteins to the nucleosome 35 , 36 , low linker histone concentrations or subtype variations 36 , inhomogeneous distributions of post-translational modifications 37 , and the disordered nature of the linker histone protein 38 can independently give rise to a plethora of nucleosome orientations and interactions. In concert, these factors can further amplify or control chromatin polymorphism 34 , 37 , 39 .…”
Section: Introductionmentioning
confidence: 99%